2010
DOI: 10.4297/najms.2010.2365
|View full text |Cite
|
Sign up to set email alerts
|

Nucleos(t)ide analogues treatment outcome in genotype B and C chronic hepatitis B

Abstract: Background:Hepatitis B genotypes influence the course and severity of the disease.Aim:To compare the treatment outcome of chronic hepatitis B genotype B and C patients after treating with nucleos(t)ide analogues for six months.Patients and Methods:Forty chronic hepatitis B patients attending the liver clinic of Hospital for Tropical diseases, Bangkok, were studied in retrospective cohort design. Six genotype B patients (15%) and thirty-four genotype C patients (85%) were treated. Serum hepatitis B viral load, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(28 reference statements)
2
1
1
Order By: Relevance
“…These results indicate that pretreatment WFA + ‐M2BP level can be helpful for predicting HBeAg loss or HBeAg SC in HBeAg positive CHB patients treated with NUC. On the other hand, our result regarding prognostic significance of pretreatment high viral load of HBV DNA linked to HBeAg SC ( P = 0.0227, HR = 6.374) is in line with previous reports …”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…These results indicate that pretreatment WFA + ‐M2BP level can be helpful for predicting HBeAg loss or HBeAg SC in HBeAg positive CHB patients treated with NUC. On the other hand, our result regarding prognostic significance of pretreatment high viral load of HBV DNA linked to HBeAg SC ( P = 0.0227, HR = 6.374) is in line with previous reports …”
Section: Discussioncontrasting
confidence: 96%
“…In our data, however, the 1‐ and 3‐year cumulative HBeAg SC rates were 8.8% and 29.0%, respectively, which were lower than previously reported data. These may be attributed to differences of baseline characteristics such as race or HBV genotype between studies …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A significant association was revealed after adjustment by multivariate multinomial logistic regression (Table 5). Similarly, a previous study reported a significant correlation between ALT normalization at the six month and successful virological outcome at one year among the NA-treated, Thai, CHB patients infected with genotype B and C HBV viruses [30]. The current study result confirmed that ALT normalization at six months after commencing NA treatment significantly predicts undetectable HVB DNA and concomitant biochemical remission and immunological recovery (aRRR 6.67, CI 1.79-24.87).…”
Section: Pretreatment Alt 15 Times Higher Than Uln As Predictor For supporting
confidence: 87%